Navigating Esthetic Challenges: Immediate Implant Placement and Comprehensive Restorative Solutions-A Clinical Case With 2-Year Follow-Up Study - Gerardo Guzman-Perez; Carlos A. Jurado; Saad Alresayes; Franciele Floriani; Silvia Rojas-Rueda; Akimasa Tsujimoto (Wiley, 2024)
Conclusions: Single immediate implant-supported crowns in the esthetic zone were able to fulfill the patient's esthetic expectations.